Health Guidelines with a personalist vision to implement sexuality education programs for adolescents - Peru - Miranda Palacios, Rocío (2018)
Reality shows us that sexuality education is being addressed poorly either because it is reduced to mere genitality, giving a biological or cultural approach, or because governments aim to provide young people in schools a purely instrumental sex education bringing as a result a trivialization of sexuality in adolescents. The aim of this research is to establish guidelines for the implementation of health education programs sexuality, with personalist vision for adolescents in Peru, based on complementarity or integrity.